(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The percentage of people who live in cities is currently 54% and is projected to increase to 66% by 2050. Due to the acceleration of rural migration and the current concentration of money in urban areas, this percentage in Iran’s northwest cities is greater than 62%. With a focus on the Kurdistan area, this paper’s objective is to analyze the main factors influencing sustainable cities in Iran’s Northwestern cities. The implemented approach is descriptive-analytical, based on library research and software analysis in the scenario wizard and Mic Mac frame. Using the snowball and Delphi sampling techniques, a continuous sample of 70 people with the appropriate executive and scientific knowledge and experience about smart cities was chosen, and their opinions were sought out at various points throughout the research. The current study’s findings indicated that urban sustainability in Iran’s northwest cities was undesirable and that many smart urban development indicators needed a higher viability percentage. With two iterations of data analysis, the stability index of urbanization status in the study area shows 96.7%, indicating the high accuracy of the current study. In contrast, metrics like recycling accessibility (98), spatial sustainability (96), and strategic urban planning (94) are more beneficial in developing smart sustainable cities in northwest Iran. Finally, some solutions are presented to increase the capacity of smart urban sustainable development in the study area.